2013
DOI: 10.1186/2193-1801-2-350
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of axillary ultrasound in preoperative nodal staging of breast cancer - size of metastases as limiting factor

Abstract: Since the performance of surgical procedures of the axilla in the treatment of early breast cancer is decreasing, the role of axillary ultrasound (AUS) as staging procedere has newly to be addressed. The aim of this study was to determine which patient or histopathological characteristics are related to false-negative AUS. In a retrospective study design data of 470 women with primary breast cancer were collected from patient charts and imaging and pathology records were reviewed. True positive and false negat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
49
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 26 publications
4
49
2
Order By: Relevance
“…All of these patients at the Mayo Clinic Rochester were clinically node-negative by preoperative axillary ultrasound (AUS) with or without fine-needle aspiration (FNA) biopsy. Recently, we have published our data from the University Hospital Rostock with an SLN-positive rate of 21.1% [14].…”
Section: Timing Of Axillary Procedures In the Neoadjuvant Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…All of these patients at the Mayo Clinic Rochester were clinically node-negative by preoperative axillary ultrasound (AUS) with or without fine-needle aspiration (FNA) biopsy. Recently, we have published our data from the University Hospital Rostock with an SLN-positive rate of 21.1% [14].…”
Section: Timing Of Axillary Procedures In the Neoadjuvant Settingmentioning
confidence: 99%
“…With regard to the higher costs and possible side effects, PET/CT and MRI do not have a place in routine axillary staging. Finally, we have to take into account that exclusion of nodal metastatic infiltration is impossible with any imaging technique in about 25% of nodal metastases due to a size of ≤ 5 mm, which is below the reliability for detection [14].…”
mentioning
confidence: 99%
“…Other groups reported lower rates of between 13% [27] and 17.6% [28]; however, another German group recently published a comparable SLN-positive rate of 21.1% [29]. The rate of positive SLN is expected to decrease in the era of breast cancer screening.…”
Section: Discussionmentioning
confidence: 94%
“…Therefore, not only the role of ALND but also that of SLNB itself is under discussion. Increasingly precise and efficient preoperative axillary imaging still misses about 25% of axillary metastatic disease -especially in cases with metastases of 5 mm and thus below the level of detection [29]. Wang et al [30] recently published a meta-analysis that not only reported SLNB false-negative rates of up to 22.9%, but also failed to find significantly different rates in overall survival, disease-free survival and local axillary recurrence with SLNB alone versus ALND.…”
Section: Discussionmentioning
confidence: 99%
“…A positive correlation doi: 10.7243/2057-1631-4-1 has been reported between the preoperative USB diagnosis of metastatic disease and the underlying prevalence of ALN metastases [9]. Further studies have also confirmed that the sensitivity of US and USB depends on the extent of axillary tumor burden [10][11][12]. Meta-analysis studies have reported that preoperative USB of the axilla is accurate for initial staging of women with invasive breast cancer [9] and is a useful step in the process of axillary staging [13].…”
Section: Introductionmentioning
confidence: 90%